1991
DOI: 10.7901/2169-3358-1991-1-571
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Nutrients to Enhance Biodegradation for the Remediation of Oil Spilled on Beaches1

Abstract: Laboratory studies were conducted to determine the fate of fertilizers proposed for application to the Alaska shoreline in support of the Alaskan Oil Spill EPA Bioremediation Project. Fertilizer application is thought to provide indigenous organisms with nutrients that appear to be limited on ocean beaches. The experiments were developed strictly to test the durability, release rates, and application procedures of a variety of fertilizer types. The effects of tidal movement on a beach were simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…Failure of the bioremediation treatment was attributed to the rapid loss of nutrients and an acute toxic response by the natural microflora to 'unweathered' condensate. Similar losses of this oleophilic nutrient from oiled sediments have been subsequently observed in laboratory studies [31] and field trials [32].…”
Section: Addition Of Nutrientssupporting
confidence: 76%
See 1 more Smart Citation
“…Failure of the bioremediation treatment was attributed to the rapid loss of nutrients and an acute toxic response by the natural microflora to 'unweathered' condensate. Similar losses of this oleophilic nutrient from oiled sediments have been subsequently observed in laboratory studies [31] and field trials [32].…”
Section: Addition Of Nutrientssupporting
confidence: 76%
“…In this instance, bioremediation was adopted as a prime cleanup strategy. Following laboratory experiments which demonstrated the potential for bioremediation [5,53], laboratory and field experiments were conducted to evaluate the effectiveness of bioremediation agents that included an oleophilic fertilizer [7,15,54], dissolved water-soluble [5,54] and slow-release inorganic fertilizer formulations [5,7,31], and microbial inocula [21]. By measuring changes over time in the oil composition, relative to hopane, a stable high-molecular weight hydrocarbon present in the oil when spilled, the rate and extent of oil biodegradation was quantified with a high level of statistical confidence.…”
Section: Application and Validation During Spill Response Operationsmentioning
confidence: 99%
“…~ apply over a large surface area and were found to adhere tightly to the oiled beach material and worked their way down under the cobble where they were difficult to dislodge. Nutrient release characteristics, which were determined in simple laboratory test systems (Safferman 1992;Glaser et al 1991), showed that much of the nitrogen (ammonia and nitrate) and phosphorus (phosphate) released from the granules occurred in the first 24-72 hours. However, sufficient quantities continued to be released steadily for a considerable time thereafter.…”
Section: Choice Of Fertilizer Formulationsmentioning
confidence: 99%
“…유류에 오염된 토양환경을 정화하기 위한 생물정화기술 (Bioremediation)은 토착미생물에 의한 유류화합물의 분해를 가속시킬 수 있는 물질 또는 유류분해미생물을 첨가하거나 조작하는 기술을 일컫는다 [3,4,12,19].…”
Section: 서 론unclassified